Oxidative dehydrogenation of ethane: catalytic and mechanistic aspects and future trends. (17th February 2021) - Najari, Sara; Saeidi, Samrand; Concepcion, Patricia; Dionysiou, Dionysios D.; Bhargava, Suresh K.; Lee, Adam F.; Wilson, Karen
Abstract : Ethane oxidative dehydrogenation (ODH) is an attractive, low energy, alternative route to reduce the carbon footprint for ethene production, however, the commercial implementation of ODH processes requires catalysts with improved selectivity. Abstract : Ethene is a commodity chemical of great importance for manufacturing diverse consumer products, whose synthesis via crude oil steam cracking is one of the most energy-intensive processes in the petrochemical industry. Oxidative dehydrogenation (ODH) of ethane is an attractive, low energy, alternative route to ethene which could reduce the carbon footprint for its production, however, the commercial implementation of ODH requires catalysts with improved selectivity. This review critically assesses recent developments in catalytic technologies for ethane ODH, and discusses how insight into proposed mechanisms from computational studies, and CO2 assisted ethane dehydrogenation (CO2 -DHE), provide opportunities for economically viable processes to meet growing demands for ethene while reducing carbon emissions. Future trends and emerging technologies for ethane ODH are also discussed.